Phenomenological research in education. A systematic overview of German phenomenological pedagogy from the beginnings up to today - Malte Brinkmann (University of Bologna, 2016)
The article provides a systematic overview of the most important approaches in German phenomenological pedagogy to the present: Fischer, Bollnow, Buck, Loch, Rombach, Fink, Schütz, Lippitz and Meyer-Drawe. Phenomenological pedagogy as both theory and empirical research aims at redefining traditional theories of Bildung, learning and education in empirical and systematic ways. They are seen as processes of experience, which take place in a horizon of phenomena of (inter-)generationality, embodiment, responsivity, foreignness and power. The phenomenological methodology combines the question of the subject matter with the methods of description, reduction and variation as guiding concepts. This phenomenological approach differs from hermeneutic and social-theoretical methods. In recent times, epistemological questions are expanded to a genealogical dimension, and methodological approaches are enriched by ethnographical and videographical instruments.